INTEGRATING ENGLISH LANGUAGE LEARNING AND SCIENCE EXPLORATION TO DEVELOP EARLY CHILDHOOD MULTILINGUAL LITERACY - Budiyati (CV. RADJA PUBLIKA, 2025)
This study aims to examine the integration of English language learning and science exploration in an effort to develop early childhood multilingual literacy. A qualitative approach with a case study method was used to explore learning practices in one of the PAUD institutions that implemented hands-on experience-based thematic learning. Data were collected through observation, interviews, and documentation, and then analyzed thematically. The results of the study show that the integration of English in science exploration activities is able to improve the understanding and use of foreign language vocabulary contextually by children. Children show progress in recognizing vocabulary, responding to instructions, and using language in the context of experiments or play activities. In addition, this approach encourages the growth of curiosity and active involvement of children in the learning process. However, the limitations of teachers in English proficiency and the need for parental involvement are challenges in themselves. This study emphasizes the importance of cross-disciplinary learning design that is contextual, applicative, and in accordance with the characteristics of early childhood development to build the foundation of multilingual literacy from an early age.